Abraham: Friend of God - Penny Frank; Tony Morris (UK USA Lion Publishing, 1985)
An illustrated retelling of the Old Testament passages describing events in the life of Abraham.
GB8419727 bnb Australia
"A Lion book"--Page 4 of cover. color illustrations
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Patriarchs (Bible) -- Biography -- Juvenile literature; Theology